2019
DOI: 10.1038/s41591-019-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of neoadjuvant PD-1 blockade predicts clinical outcomes in resectable melanoma

Abstract: Immunologic responses to anti-PD-1 therapy in melanoma patients occur rapidly with pharmacodynamic T cell responses detectable in blood by 3 weeks. It is unclear, however, whether these early blood-based observations translate to the tumor microenvironment. We conducted a study of neoadjuvant/adjuvant anti-PD-1 therapy in stage III/IV melanoma. We hypothesized that immune reinvigoration in the tumor would be detectable at 3 weeks and this response would correlate with disease-free survival. We identified a rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
418
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(457 citation statements)
references
References 39 publications
33
418
1
5
Order By: Relevance
“…Our findings suggest that the increased surface expression of CTLA‐4 is uniquely maintained in CD4 + TIL after activation followed by 14–21 day culture. Similar findings were reported in melanoma comparing TIL phenotypes ex vivo following exposure to a single dose of anti‐PD1; however both studies reported a positive correlation with the presence of CD8 + PD‐1 hi CTLA‐4 hi , not with the CD4 population .While the observation that patients who experienced tumor regression to anti‐PD‐1 therapy do not experience a sustained elevation of CTLA‐4 on CD4 + TIL is interesting, additional patients who experienced tumor regression would be needed to see if the pattern holds. Nevertheless, it does suggest that inhibition through CTLA‐4 may limit the efficacy of the therapy and argues for testing the combination of anti‐PD‐1 and CTLA‐4 blockade in rare solid tumors.…”
Section: Resultssupporting
confidence: 71%
“…Our findings suggest that the increased surface expression of CTLA‐4 is uniquely maintained in CD4 + TIL after activation followed by 14–21 day culture. Similar findings were reported in melanoma comparing TIL phenotypes ex vivo following exposure to a single dose of anti‐PD1; however both studies reported a positive correlation with the presence of CD8 + PD‐1 hi CTLA‐4 hi , not with the CD4 population .While the observation that patients who experienced tumor regression to anti‐PD‐1 therapy do not experience a sustained elevation of CTLA‐4 on CD4 + TIL is interesting, additional patients who experienced tumor regression would be needed to see if the pattern holds. Nevertheless, it does suggest that inhibition through CTLA‐4 may limit the efficacy of the therapy and argues for testing the combination of anti‐PD‐1 and CTLA‐4 blockade in rare solid tumors.…”
Section: Resultssupporting
confidence: 71%
“…10c). These results suggest that it may be feasible, though challenging, to monitor the clonal tumor-specific T cell response to checkpoint blockade in the blood 49,50 .…”
Section: Resultsmentioning
confidence: 99%
“…After therapy, an increase of Ki-67+, PD-1+, CD8+ T cells displaying an effectorlike phenotype (HLA-DR+, CD38+, Bcl-2 low ), costimulatory molecules (CD28+, CD27+, ICOS+), high levels of PD-1 and co-expression of CTLA-4 was observed in patients responding to therapy (135,140). In the same patients, the expansion of CD39+, CD8+ T cells was observed a few days after a single dose of anti-PD-1 in a neoadjuvant setting (145). Tracking TCR clones and transcriptional phenotypes in basal cell carcinoma (BCC)…”
Section: Cd8+ T Cellsmentioning
confidence: 90%